Perbaikan kualitas air pada peternakan ayam petelur dengan penggunaan filter zeolit antimikroba - A’la, Nurul; Abidin, Zaenal; Arief, Irma Isnania (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
Drinking water in chicken farms is often contaminated with microbes that can cause several diseases in chickens. E. coli is a microbial pathogen treated with antibiotics and chlorine-based disinfectants, but it can leave residues in chicken tissues and cause resistance, threatening animal, human, and environmental health. So, it needs other alternatives, such as the use of antimicrobial zeolit filters that are made from natural materials and do not leave harmful residues. This study aims to determine the quality of chicken drinking water after applying antimicrobial zeolit filters and analyze the strategy for implementing filters in chicken farms. The study was conducted at Antoni Layer Farm, Sukabumi, West Java, from January to July 2022. Data was collected through experimentation, observation, interview, and literature study. Microbial data were analyzed using the BAM method and compared to PerMenKes (2017) and SNI (2009). Strategy analysis was conducted using SWOT analysis. The results showed that antimicrobial zeolit filters effectively reduced the number of Escherichia coli and Salmonella in chicken drinking water without leaving residues that are harmful to health and the environment and have the potential to develop. In conclusion, antimicrobial zeolit filters on poultry farms contribute to sustainable development goals by improve water quality on layer farms.